2009
DOI: 10.1037/a0012989
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing decisional balance in an adolescent sun protection intervention: Mediating effects and theoretical interpretations.

Abstract: The Transtheoretical model (TTM) integrates principles of operant learning, such as stimulus control and reinforcement, and psychological factors, such as decisional balance. Understanding interrelationships between decisions, behavior, and consequences from multiple theoretical perspectives can advance theory and inform development of more effective interventions. This analysis examined the mediating effects of a special case of the decisional balance construct where the pros of competing behaviors (i.e. sun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 50 publications
(77 reference statements)
2
31
0
Order By: Relevance
“…Basic principles of positive reinforcement [18, 19] and behavioral economics [2025] are integrated into many theoretical approaches (e.g., Transtheoretical Model [26, 27], Social Cognitive Theory [28, 29], and Ecological Models [30, 31]) and have been proposed as unifying behavior change principles behind preventive medicine [32]. Positive reinforcement should be preferred because gain-based approaches produce fewer psychological side effects (e.g., aggression, frustration) than approaches based on aversive control such as penalties (e.g., loss of reward) [33] and may be more effective than non-contingent or interval-based (delayed) reinforcement for long-term behavior change [20, 31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Basic principles of positive reinforcement [18, 19] and behavioral economics [2025] are integrated into many theoretical approaches (e.g., Transtheoretical Model [26, 27], Social Cognitive Theory [28, 29], and Ecological Models [30, 31]) and have been proposed as unifying behavior change principles behind preventive medicine [32]. Positive reinforcement should be preferred because gain-based approaches produce fewer psychological side effects (e.g., aggression, frustration) than approaches based on aversive control such as penalties (e.g., loss of reward) [33] and may be more effective than non-contingent or interval-based (delayed) reinforcement for long-term behavior change [20, 31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Higher scores (1 = strongly disagree, 5 = strongly agree) indicate greater beliefs in the effectiveness of sunscreen. Outcome evaluations for skin protection were assessed using a decisional balance scale calculated by dividing the average response to items on a pros of skin protection scale by the average response to items on a cons of skin protection scale (1 = not very important, 5 = extremely important) 25, 39, 40. A sample pros item is “Using sunscreens allows me to enjoy the outdoors with less worry.” A sample cons item is “Sunscreen is more trouble than it’s worth.”…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores (1 = low, 5 = high) indicate a greater belief in one’s ability to tan without burning. Outcome evaluations for UV exposure was assessed using a decisional balance scale calculated by dividing the average response to items on a pros of UV exposure scale by the average response to items on a cons of UV exposure scale (1 = not very important, 5 = extremely important) 25, 39, 40. A sample pros item is “I look better when I have a tan.” A sample cons item is “Having a tan is unhealthy.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The core of Prochaska's Stage of Change model is based on the following five stages: 1) Pre-contemplation: no intention to change behavior in the foreseeable future; 2) Contemplation: being aware of the problem, and thinking about changing behavior; 3) Preparation: intention to change behavior in the next month, and have successfully tried to change behavior in the past year; 4) Action: behavior is changed in order to overcome a problem, which requires time and energy; and 5) Maintenance: prevent relapse, consolidate gains attained during action, and maintenance of action for ≥6 months [10]. This model has been used to investigate and characterize numerous health behaviors among adolescents, including smoking cessation [11][12][13], substance abuse [12,14], sun protection [15], fruit and vegetable consumption [16], dietary adherence [17], contraceptive use [18], and physical activity [19]. For example, results from a study by Dino et al indicated that adolescents' stage of change at baseline predicted smoking cessation intervention outcomes three months post-baseline [11].…”
Section: Introductionmentioning
confidence: 99%